Definition of CD4 Immunosignatures Associated with MTB - Lindestam Arlehamn, Cecilia S.; Sette, Alessandro (Frontiers in Immunology, 2014)
We have recently described the first true genome-wide screen for CD4+ T cell reactivity directed against MTB in latent TB infected individuals. The approach relied on predictions of HLA binding capacity for a panel of DR, DP and DQ alleles representative of those most commonly expressed in the general population, coupled with high throughput ELISPOT assays. The results identified hundreds of novel epitopes and antigens, and documented the novel observation that T cells in latent MTB infection are confined to the CXCR3+CCR6+ phenotype and largely directed against three antigenic “islands” within the MTB genome. In parallel, we have made generally available to the scientific community the technical approaches and reagents developed in the process, such as motifs, algorithms, and binding assays for several common HLA class II alleles, and a panel of single allele HLA class II transfected cell lines representative of the most frequent specificities in the general population. Recent efforts have been focused on characterization of epitopes and antigens recognized by patients with active TB and individuals vaccinated with BCG, with the aim of providing the first systematic evaluation of the overlap between latent, active and BCG cohorts. The definition of a broad range of epitopes restricted by common HLA molecules, will facilitate development of diagnostic reagents, allow a rigorous evaluation of T cell responses associated with TB infection in humans, and enable the evaluation of the immunogenicity of different vaccine candidates. Furthermore, it might suggest new candidates for vaccine and diagnostic development.